Is maternal employment related to childhood obesity? - Wencke Gwozdz (IZA World of Labor, 2016)
Childhood obesity has been rising steadily in most parts of the world. Popular speculation attributes some of that increase to rising maternal employment. Employed mothers spend less time at home and thus less time with their children, whose diets and physical activity may suffer. Also, children of working mothers may spend more time in the care of others, whose childcare quality may vary substantially. While a majority of US studies support this hypothesis and have clear policy implications, recent studies in other countries are less conclusive, largely because institutional arrangements differ but also because methodologies do.
Keywords: J13; 330; childhood obesity; maternal employment; childcare